An Américain in Africa: The Transatlantic Creations of Paul Belloni du Chaillu - Adam Lifshey (Journal of Transnational American Studies, 2011)
The most popular American writer the year the Civil War began was not, perhaps, American. A nation on the verge of splitting asunder enthusiastically consumed stories of its national identity being consolidated in Africa in a book by Paul Belloni du Chaillu, a young man of ambiguous origins and spectacular credibility issues. His 1861 bestseller Explorations and Adventures in Equatorial Africa about his pith-helmeted exploits marked him as an intrepid scientist or armchair fantasist or, possibly, both. Regardless, his rise from anonymity to transatlantic sensation in a moment of acute national crisis suggests that something important was created and perceived in the shifting identitarian signs of his person and his work. Du Chaillu was not simply a European adventurer or American journalist or African homesteader, all of which he became, for capital of all sorts moved through him in multinational and continental forms. As a result, Du Chaillu deserves a space of prominence in any configuration of a nineteenth-century transatlantic canon. He also merits attention as the author of the last great antebellum American narrative. The fact that the qualifier “American” in that statement is utterly debatable is entirely, given 1861, the point.